The characteristics of swelling and biodegradation tests of bovine amniotic membrane-hydroxyapatite biocomposite - Agustantina, Titien Hary; Munadziroh, Elly; Yuliati, Anita; Bahtiar, Muhammad Riza Hafidz; Octarina; Salma, Rizki Fauziah; Meyranti, Ajeng Putri; Razak, Fathilah Abdul (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: A good biocomposite is a structure that can provide opportunities for cells to adhere, proliferate, and differentiate. It is affected by the characteristics of a material. As bone tissue regeneration occurs, biomaterials must have a high swelling ability and low biodegradability. The high swelling capability will have a larger surface area that can support maximal cell attachment and proliferation on the biocomposite surface, which accelerates the regeneration process of bone defects. Purpose: The study aimed to analyze the characteristics of swelling and biodegradation of bovine amniotic membrane-hydroxyapatite (BAM-HA) biocomposite with various ratios. Methods: The BAM-HA biocomposite with a ratio of 30:70, 35:65, and 40:60 (w/w) was synthesized using a freeze-dry method. The swelling test was done by measuring the initial weight and final weight after being soaked in phosphate-buffered saline for 24 hours and the biodegradation test was done by measuring the initial weight and final weight after being soaked in simulated body fluid for seven days. Results: The swelling percentage of BAM-HA biocomposite at each ratio of 30:70, 35:65, and 40:60 (w/w) was 303.90%, 477.94%, and 574.19%. The biodegradation percentage of BAM-HA biocomposite at each ratio of 30:70, 35:65, and 40:60 was 9.43%, 11.05%, and 12.02%. Conclusion: The BAM-HA biocomposite with a ratio of 40:60 (w/w) has the highest swelling percentage while the 30:70 (w/w) ratio has the lowest percentage of biodegradation.